Prevalence and antimicrobial sensitivity profile of uropathogens in a tertiary care hospital of Dhaka city (Bangladesh Journal of Medical Microbiology, 2020)
Urinary tract infection (UTI) is one of the most frequently occurring infections worldwide seeking medical attentions. The etiology of UTI and the antimicrobial sensitivity pattern of uropathogens vary in regions and change through time. This study aims to evaluate the pathogens responsible for causing UTI and analyze the antimicrobial sensitivity pattern of the isolated uropathogens. This cross sectional study was carried out in the Department of Microbiology, Bangladesh Medical College, Dhaka over a period of January 2018 to December 2019. Out of 11,274 urine samples, 1452 (12.88%) were positive for uropathogens by culture. Among these 1452 isolates, majority of them 936 (64.46%) were isolated from females. Escherichia coli 899 (61.91%) was the predominant organism followed by Enterococccus species 168 (11.57%), Klebsiella species 140 (9.64%), Enterobacter species 137 (9.44%). Escherichia coli showed high rate of sensitivity to nitrofurantoin 79.76%, gentamicin 75.31%, amikacin 88.65%, imipenem 97.89% and meropenem 80.87%. Pseudomonas species showed high rate of sensitivity to imipenem 70.45%. Enterococcus species showed high rate of sensitivity to vancomycin 94.05%, imipenem 70.83% and linezolid 79.76%. UTI is a very common problem and rate of antimicrobial resistance is increasing day by day. Therefore, each institution should have an antibiotic policy based on the local antibiogram which is to be renewed regularly.Bangladesh J Med Microbiol 2020; 14 (2): 3-11